Effects of Phyllanthus niruri on the severity of the common cold in children - Ari Dwi Ratna Kusumaningrum; Sumadiono Sumadiono; Yati Soenarto (Paediatrica Indonesiana, 2012)
Background Common cold is a selfô€€µlimited disease, howeverit poses a significant burden on productivity and communityhealth. Unfortunately, there has been no standard medicationfor childhood common cold, whereas some herbs \\lith immuneô€€µmodulating properties, such as Phyllanthus niruri extract (PNE),might be beneficial but has not been thoroughly studied.Objective To evaluate the effect of PNE administration on theseverity of common cold symptoms in children.Methods We performed a randomized, doubleô€€µblind, controlledtrial in children aged 2ô€€µ6 years who were diagnosed Mth a commoncold at primary health care centers in Sewon and Jetis in Bantul,as well as in Gondomanan and Gedongtengen in Yogyakarta.Subjects were collected by consecutive sampling and parentswere interviewed. We assessed illness severity by Hemila scoringfor the common cold.Results A total of 100 subjects were included Mth 50 subjects ineach intervention group. After treatment, there was no significantdifference in common cold severity between the PNE and thecontrol groups for all symptom score components, including cough(0.87 vs 0.71, Pô€€½0.36), nasal symptom (0.90 vs 1.10, Pô€€½0.54),coryza ( 0.44 vs 1.10, P=0.54), and systemic symptom (0.10 vs0.10, Pô€€½0.94).Conclusion Administration of PNE for 6 days did not provide asignificant benefit in reducing the severity of the common coldcompared to placebo in children aged 2 - 6 years. [PaediatrIndanes.2012;52:346-51].